Theoretical Study on the Formation of H‐ and O‐Atoms, HONO, OH, NO, and NO2 from the Lowest Lying Singlet and Triplet States in Ortho‐Nitrophenol Photolysis. Issue 12 (26th September 2016) - Vereecken, L.; Chakravarty, H. K.; Bohn, B.; Lelieveld, J.
ABSTRACT: The photolysis of nitrophenols was proposed as a source of reactive radicals and NO x compounds in polluted air. The S0 singlet ground state and T1 first excited triplet state of nitrophenol were investigated to assess the energy dependence of the photofragmentation product distribution as a function of the reaction conditions, based on quantum chemical calculations at the G3SX//M06–2X/aug‐cc‐pVTZ level of theory combined with RRKM master equation calculations. On both potential energy surfaces, we find rapid isomerization with the aci ‐nitrophenol isomer, as well as pathways forming NO, NO2, OH, HONO, and H‐, and O‐atoms, extending earlier studies on the T1 state and in agreement with available work on other nitroaromatics. We find that accessing the lowest photofragmentation channel from the S0 ground state requires only 268 kJ/mol of activation energy, but at a pressure of 1 atm collisional energy loss dominates such that significant fragmentation only occurs at internal energies exceeding 550 kJ/mol, making this surface unimportant for atmospheric photolysis. Intersystem crossing to the T1 triplet state leads more readily to fragmentation, with dissociation occurring at energies of ∼450 kJ/mol above the singlet ground state even at 1 atm. The main product is found to be OH + nitrosophenoxy, followed by formation of hydroxyphenoxy + NO and phenyloxyl + HONO. The predictions are compared against available experimental data.